Retinal tau phosphorylation in Alzheimer's disease : A mass spectrometry study - Santiago, Jessica ; 0009-0000-9772-7510; Pocevičiūtė, Dovilė ; 0009-0001-7400-6339; Vogel, Jacob; Brinkmalm, Gunnar; Wennström, Malin (Neurobiology of Disease, 2025)
Introduction: Most neurodegenerative diseases, including Alzheimer's disease (AD) and multiple sclerosis (MS), feature abnormal tau phosphorylation (p-tau) in the brain. Prior immunostaining studies have shown p-tau accumulation in the AD retina, suggesting it may mirror brain tau pathology. Methods: We used mass spectrometry to quantify p-tau peptides in matched retinal and hippocampal samples from non-demented controls (NC, n = 8), AD (n = 12), and MS (n = 4). We compared p-tau levels across diagnoses and analysed correlations between retinal p-tau variants, hippocampal p-tau, and neuropathological changes. Results: Tau peptides phosphorylated at T181, S199/S202, T231, T231 + T235, S396 + T403/S404, and T403/S404 were detected in retinas. Total tau phosphorylation and phosphorylation at S199/S202 and T231 were significantly higher in AD cases compared to NC. These two, along with p-tau S396 + T403/S404, were also higher in cases with high amyloid-beta (Aβ) Braak stages compared to those with low Aβ Braak stages. Higher Aβ stages were also correlated with higher peak intensities of p-tau S199/S202 and S396 + T403/S404, and retinal p-tau S396 + T403/S404 and T403/S404 correlated with neurofibrillary tangle (NFT) Braak stages. Additionally, p-tau S396 + T403/S404 in the retina was associated with corresponding phosphorylation in the hippocampus. Conclusion: Our findings reveal both overlapping and distinct p-tau patterns in retina and hippocampus, with a notable link for p-tau S396 + T403/S404. This enhances our understanding of tauopathies in both tissues and supports retinal tau as a promising biomarker for AD diagnosis and monitoring.
Publisher Copyright: © 2025 The Authors
Keywords: Alzheimer's disease; Mass spectrometry; P-tau; Retina; Tau